Development Of Environmental Factors In Classroom Design Recommendation For Children With Autism Spectrum Disorder - Mamat@Muhamad, Roziana (2020)
Typical learning environment at a centre for children with autism spectrum disorder (ASD) are designed based on healthy normal children. Ideally, the learning environment for these children should complement their unique functional, emotional and behavioural requirements as inappropriateness will cause distraction, uncomfortable condition and occurrence of undesirable behaviour. Hence ergonomic intervention needs to be introduced. This research study the impact of five different factors of the physical classroom environment on children understanding instructions and their attention span in the classroom. Observation on behaviour, emotion and cognitive of those children carried out for each physical classroom environment factor. They were subjected to two types of experiments for each physical environment factors. Qualitative and quantitative methods were carried out. Two experiments were conducted to measure individual’s response time to instruction (speed of understanding) and time to complete a task (a measurement of attention span). The experiment deployed eleven children with ASD aged between five to nine years old. Their mental age is between four to five years. A control group with normal children age four to five years was also used for comparison. The physical environment factors being studied are sound decibel, sound frequency, the intensity of the light intensity, type of colour and temperature within the classroom. For the children with ASD, five different levels of each factor were set up for each experiment. Pre-tests (current condition) and post-tests (intervention condition) approach are only applied for sound. The other physical factors were done using typical experimental techniques. Observation method was deployed in all physical factors to study the children with ASD behavioural, emotional and cognitive reaction. Statistical analysis tools are used to quantitatively evaluate the effect of environmental factors on the response time and attention span. Qualitative analysis tools were executed to assess the behavioural, emotional and cognitive reaction. The finding showed that ergonomic intervention caused significant improvement in the speed of understanding and attention span during task performing for the children with ASD compared to their current learning environment. Restlessness and uncomfortable behaviour had also decreased significantly within an optimum range of each physical factor. However, their performance is still slower than normal children. Those optimal values of the environmental factor are recommended in the design of the learning environment specifically for children with ASD in Malaysia.